The Numerical Ability on Student Achievement of STIKOM Tunas Bangsa - Ika Okta Kirana; Zulaini Masruro Nasution; Fitri Anggraini; Bahrudi Efendi Damanik (At-Tarbawi: Jurnal Pendidikan, Sosial dan Kebudayaan, 2023)
The purpose of this study was to determine the effect of students' numerical ability on learning achievement in terms of the student achievement index at STIKOM Tunas Bangsa Pematangsiantar. This type of research is quantitative research. The sample in this study were second semester students from various departments at STIKOM Tunas Bangsa. Many samples used in this study amounted to 80 students. In collecting data used documentation and test instruments. To determine the influence used simple regression analysis. The results of the regression analysis obtained a significance value of <0.05, namely 0.000 <0.05, meaning that there is a significant influence on students' numeracy literacy skills on learning achievement. As for the coefficient of determination, a value of 0.215 is obtained, which means that the effect of the independent variable (numerical ability) on the dependent variable (learning achievement) is 21.5%. linearity test obtained sig. deviation from linearity > 0.05 or 0.517 > 0.05, meaning that the data has a linear pattern with the regression equation Y = 3.061 + 0.008 X. The correlation coefficient of the research data is 0.465, thus the magnitude of the contribution of numeracal ability to learning achievement is 46.5% , while the rest are influenced by other factors not observed in this study.